Study on integrated sensing and communication for 6G RAN - Shiqiang SUO; Shenghao XU; Ting ZENG; Qiusha GONG; Ke WANG (Dianxin kexue)
The integrated sensing and communication technology has become one of the important research directions for 6G system.The necessity of integrated sensing and communication at the air inter face was analyzed and summarized, as not only for improving the service capacity for 6G system but also for effectively improving the spectrum utilization.One integrated sensing and communication scheme at the air interface level for 6G RAN was proposed, including the high level framework of RAN system, the multiplexing mode of wireless sensing signal and communication signal, the design of integrated channel/signal, etc.for further study.The challenges of integrated sensing and communication at the air interface were analyzed.It was pointed out that integrated sensing and communication at the air interface would have an important impact on the design of 6G RAN protocol stack, which needed to be focused on.